Voice prosthesis rehabilitation after total laryngectomy: are satisfaction and quality of life maintained over time? - GALLI, A. (Acta Otorhinolaryngol Ital, 2019)
Total laryngectomy is the standard of care for advanced laryngeal/hypopharyngeal cancer. Effective voice rehabilitation is mandatory and tracheo-oesophageal speech (TES) has progressively gained approval. In 2011, we evaluated quality of life (QoL) and satisfaction after TES rehabilitation, demonstrating its efficacy in highly motivated subjects. The aim of the present study was to investigate whether those results are maintained over time within the same selected cohort. 15 of 24 patients were left with a minimum 12 year-follow up after voice prosthesis (VP) implantation. Short Form 36-Item Health Survey (SF-36) for QoL assessment and a study-specific structured questionnaire for evaluation of TES-related satisfaction were employed. The 9/24 patients who dropped out from the follow-up were excluded from the original count and the former results were recalculated. A control group of subjects with minor ENT diseases was used for SF-36 analysis. Many SF-36 items (RP, BP, SF, RE) significantly improved over time, approaching the results of the control group. VP duration also increased (6.3 ± 3.1 against 3.0 ± 1.8 months). TES-related satisfaction items did not change in a statistically significant way. Three patients (20.0%) would not have chosen the same kind of voice restoration: these subjects are those more distant from our institution (230 km and 462 km, respectively, against a mean distance of 15.4 ± 13.8 km for other patients). With the present work, we highlight how the striking results of TES can not only be maintained over time (i.e. TES-related satisfaction), but also substantially improve (i.e. QoL). An integrated, widespread network of centres for VP management is needed to optimise patient follow-up and allow studies on larger series.